Clinical characteristics of doxorubicin‐associated alopecia in 28 dogs. Issue 2 (15th December 2016) - Falk, Elizabeth F.; Lam, Andrea T. H.; Barber, Lisa G.; Ferrer, Lluis
Abstract : Background: Chemotherapy‐induced alopecia (CIA) is common in humans, but there are limited reports describing the clinical features of CIA in dogs. Objectives: To describe the epidemiological and clinical characteristics of doxorubicin‐associated alopecia (DAA) in canine patients at a teaching hospital from 2012 to 2014. Animals: Signalment, diagnosis, treatment protocols and clinical examination findings were recorded in 150 dogs treated with doxorubicin from 2012 to 2014. Methods: Medical records were searched retrospectively for the keywords "alopecia" and "hypotrichosis." Dogs were excluded if the causal link of hair loss was unclear. Results: Doxorubicin‐associated alopecia was reported in 28 of 150 dogs (19%). Two parameters were statistically associated with the development of DAA: coat‐type and cumulative doxorubicin dose. Dogs with curly or wire‐haired coat‐type were significantly more likely to develop DAA than dogs with straight‐haired coat‐type [χ 2 (1, N = 147) = 30, P < 0.0001]. After adjusting for sex, weight and doxorubicin dose, the odds of dogs with curly or wire‐haired coat‐type developing DAA were 22 times higher than those with straight‐haired coat‐type ( P < 0.0001). Dogs that developed DAA received a significantly higher median cumulative doxorubicin dose (103.0 versus 84.5 mg/m 2 ; P = 0.0039) than those that did not develop DAA. Conclusions and clinical importance: Dogs treated with doxorubicin may be at risk for developing DAA. This risk increases as the cumulative dose of doxorubicin increases, and with a curly or wire‐haired coat‐type. Abstract : Background – Chemotherapy‐induced alopecia (CIA) is common in humans but uncommon in dogs. There are limited reports describing the clinical features of CIA in dogs.Objectives – To describe the epidemiological and clinical characteristics of doxorubicin‐associated alopecia (DAA) in canine patients at a teaching hospital from 2012 to 2014.Conclusions and clinical importance – Dogs treated with doxorubicin may be at risk for developing DAA. This risk increases as the cumulative dose of doxorubicin increases, and with a curly or wire‐haired coat‐type.